Finerenone cardiovascular and kidney outcomes by age and sex: FIDELITY post hoc analysis of two phase 3, multicentre, double-blind trials - Bansal, Shweta; Canziani, Maria E F; Birne, Rita; Anker, Stefan D; Bakris, George L; Filippatos, Gerasimos; Rossing, Peter; Ruilope, Luis M; Farjat, Alfredo E; Kolkhof, Peter; Lage, Andrea; Brinker, Meike; et al. (BMJ open, 2024)
ObjectivesThis study aimed to evaluate the efficacy and safety of finerenone, a selective, non-steroidal mineralocorticoid receptor antagonist, on cardiovascular and kidney outcomes by age and/or sex.DesignFIDELITY post hoc analysis; median follow-up of 3 years.SettingFIDELITY: a prespecified analysis of the FIDELIO-DKD and FIGARO-DKD trials.ParticipantsAdults with type 2 diabetes and chronic kidney disease receiving optimised renin–angiotensin system inhibitors (N=13 026).InterventionsRandomised 1:1; finerenone or placebo.Primary and secondary outcome measuresCardiovascular (cardiovascular death, non-fatal myocardial infarction, non-fatal stroke or hospitalisation for heart failure (HHF)) and kidney (kidney failure, sustained ≥57% estimated glomerular filtration rate (eGFR) decline or renal death) composite outcomes.ResultsMean age was 64.8 years; 45.2%, 40.1% and 14.7% were aged <65, 65–74 and ≥75 years, respectively; 69.8% were male. Cardiovascular benefits of finerenone versus placebo were consistent across age (HR 0.94 (95% CI 0.81 to 1.10) (<65 years), HR 0.84 (95% CI 0.73 to 0.98) (65–74 years), HR 0.80 (95% CI 0.65 to 0.99) (≥75 years); Pinteraction=0.42) and sex categories (HR 0.86 (95% CI 0.77 to 0.96) (male), HR 0.89 (95% CI 0.35 to 2.27) (premenopausal female), HR 0.87 (95% CI 0.73 to 1.05) (postmenopausal female); Pinteraction=0.99). Effects on HHF reduction were not modified by age (Pinteraction=0.70) but appeared more pronounced in males (Pinteraction=0.02). Kidney events were reduced with finerenone versus placebo in age groups <65 and 65–74 but not ≥75; no heterogeneity in treatment effect was observed (Pinteraction=0.51). In sex subgroups, finerenone consistently reduced kidney events (Pinteraction=0.85). Finerenone reduced albuminuria and eGFR decline regardless of age and sex. Hyperkalaemia increased with finerenone, but discontinuation rates were <3% across subgroups. Gynaecomastia in males was uncommon across age subgroups and identical between treatment groups.ConclusionsFinerenone improved cardiovascular and kidney composite outcomes with no significant heterogeneity between age and sex subgroups; however, the effect on HHF appeared more pronounced in males. Finerenone demonstrated a similar safety profile across age and sex subgroups.Trial registration numbersNCT02540993, NCT02545049.